2016
DOI: 10.1016/j.cell.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

A Non-canonical Voltage-Sensing Mechanism Controls Gating in K2P K+ Channels

Abstract: SummaryTwo-pore domain (K2P) K+ channels are major regulators of excitability that endow cells with an outwardly rectifying background “leak” conductance. In some K2P channels, strong voltage-dependent activation has been observed, but the mechanism remains unresolved because they lack a canonical voltage-sensing domain. Here, we show voltage-dependent gating is common to most K2P channels and that this voltage sensitivity originates from the movement of three to four ions into the high electric field of an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
310
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(343 citation statements)
references
References 47 publications
32
310
1
Order By: Relevance
“…Some of the TREK-2 activators caused inhibition of TREK-1 channels, and these molecules will provide structural insights into what controls TREK channel biophysical activity and outward rectification. 34 For example, T2A3 activates TREK-2 and at higher concentrations slightly inhibits TREK-1 as well as causing less TREK-2 outward rectification. As TREK-2 rectification is also reduced by a number of other activators such as arachidonic acid, T2A3 may activate TREK-2 channels like these activators and differentially from T2A8 or T2A9 that only modestly influence rectification.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the TREK-2 activators caused inhibition of TREK-1 channels, and these molecules will provide structural insights into what controls TREK channel biophysical activity and outward rectification. 34 For example, T2A3 activates TREK-2 and at higher concentrations slightly inhibits TREK-1 as well as causing less TREK-2 outward rectification. As TREK-2 rectification is also reduced by a number of other activators such as arachidonic acid, T2A3 may activate TREK-2 channels like these activators and differentially from T2A8 or T2A9 that only modestly influence rectification.…”
Section: Resultsmentioning
confidence: 99%
“…Ashmole et al (2009) hypothesized the existence of an inner helices bundle crossing activation gate to explain voltage gating of TASK-3). The effect of voltage is quite weak, and the measured gating charge is 0.17, which is small compared with ∼2 for the ensemble of K 2P channels studied by Schewe et al (2016). Nevertheless, this can be enhanced by mutations affecting pore lining in helices TM2 and TM4 and virtually abolished by mutating the putative glycine hinge residues to alanine residues.…”
Section: Is There the Equivalent Of An Activation Gatementioning
confidence: 94%
“…Gating in response to voltage does occur in K 2P channels, although it has been largely ignored and remained poorly understood (Renigunta et al, 2015); however, recent detailed work (Schewe et al, 2016) provides a robust hypothesis of how the voltage-dependence of K 2P channels might work in the absence of a conventional voltage-sensor. It was shown that voltage dependence was present in most K 2P channels, except for TWIK-1, and relies crucially on the movement of the permeant ion and therefore on its electrochemical potential difference.…”
Section: Is There the Equivalent Of An Activation Gatementioning
confidence: 99%
See 1 more Smart Citation
“…In K2P K + channels, the permeation barrier is greatly affected by the direction of the K + flux driven by the electrochemical gradient. A model of flux-coupled gating in the multi-ion selectivity filter in the K2P K + channel has been proposed to explain the intrinsic strongly outward rectifying current-voltage relationship without extracellular or intracellular blockers [35]. The gating barrier to ion permeation within the channel pore is "driving force"-dependent because the barrier is significantly affected by the direction of the K + ion flux.…”
Section: The Roles Of the Multi-ion Single-file Pores In "Driving Formentioning
confidence: 99%